2020
DOI: 10.1186/s13578-020-00455-7
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal cargos modulate autophagy in recipient cells via different signaling pathways

Abstract: Vesicular system of mammalian cells is composed of two intracellular and extracellular vesicles systems, which contributes to the intra/intercellular communication and cellular homeostasis. These systems mediate transferring of biological molecules like proteins, nucleic acids, and lipids inside the cytoplasm, and between the cells. By the present study, authors describe molecular crosslink between exosome biogenesis and autophagy and take a certain focus on the autophagic cargos of exosomes and signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 142 publications
(191 reference statements)
0
46
0
Order By: Relevance
“…On uptake of exosomes, the delivery of exosomal cargo to recipient cells occurs and thus promotes the susceptibility of the recipient cell for virus infection. Besides, it has been confirmed that CD9 molecules participate in the entry of the protein-protein network in the MVBs membrane within exosomes [82] and thus favourably affect the loading of COVID-19 viral proteins. It was found that there is an increase in circulating exosomes that contain lung-associated self-antigens, viral antigens as well as 20S proteasome in coronavirus infections.…”
Section: Exosomes In Covid-19mentioning
confidence: 92%
“…On uptake of exosomes, the delivery of exosomal cargo to recipient cells occurs and thus promotes the susceptibility of the recipient cell for virus infection. Besides, it has been confirmed that CD9 molecules participate in the entry of the protein-protein network in the MVBs membrane within exosomes [82] and thus favourably affect the loading of COVID-19 viral proteins. It was found that there is an increase in circulating exosomes that contain lung-associated self-antigens, viral antigens as well as 20S proteasome in coronavirus infections.…”
Section: Exosomes In Covid-19mentioning
confidence: 92%
“…Notably, exosome release is inhibited by sustained activation of mTORC1, leading to intracellular accumulation of CD63-positive exosome precursors, whereas inhibition of mTORC1 by rapamycin or nutrient and growth factor deprivation stimulates exosome release, which occurs concomitantly with autophagy [ 104 ]. Exciting research focuses on the crosstalk between exosome biogenesis and autophagy that plays pivotal roles in cell homeostasis, which is disturbed in neurodegenerative diseases [ 105 , 106 ].…”
Section: Milk: a Signaling System For Postnatal Growth And Differementioning
confidence: 99%
“…An intricate relationship among autophagy and the exosome biogenesis ( Figure 1A ) occurs at different stages ( Buratta et al, 2020 ; Hassanpour et al, 2020 ; Salimi et al, 2020 ). If in some cellular contexts autophagy and exosome production act at the same time to counter cellular stress ( Kumar et al, 2014 ), in other circumstances the two processes can compensate each other.…”
Section: Crosstalk Between Autophagy and Exosome Biogenesismentioning
confidence: 99%